The Bsmoc group as a novel scaffold for the design of irreversible inhibitors of cysteine proteases - Iley, J (2015)
Carbamate and ester derivatives of the 1,1-dioxobenzo[b]thiophen-2-ylmethyloxycarbonyl (Bsmoc) scaffold react readily with thiols via a Michael addition at rates not significantly affected by the nature of the carboxylic or carbamic acid leaving group. These Michael acceptors are irreversible inhibitors of the cysteine proteases papain and human liver cathepsin B, displaying first-order kinetics with respect to inhibitor concentration. In contrast, none of the Bsmoc derivatives inhibited porcine pancreatic elastase, a serine protease. (C) 2006 Elsevier Ltd. All rights reserved.